Resveratrol treatment protects against doxorubicin-induced cardiotoxicity by alleviating oxidative damage - VELİOĞLU ÖĞÜNÇ, AYLİZ; YARAT, AYŞEN; YEGEN, BERRAK; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (TAYLOR & FRANCIS LTD, 2009)
The possible protective effects of resveratrol (RVT) against cardiotoxicity were investigated in Wistar albino rats treated with saline, saline+doxorubicin (DOX; 20 mg/kg) or RVT (10 mg/kg)+DOX. Blood pressure and heart rate were recorded on the 1st week and on the 7th week, while cardiomyopathy was assessed using transthoracic echocardiography before the rats were decapitated. DOX-induced cardiotoxicity resulted in decreased blood pressure and heart rate, but lactate dehydrogenase, creatine phosphokinase, total cholesterol, triglyceride, aspartate aminotransferase and 8-OHdG levels were increased in plasma. Moreover, DOX caused a significant decrease in plasma total antioxidant capacity along with a reduction in cardiac superoxide dismutase, catalase and Na+,K+-ATPase activities and glutathione contents, while malondialdehyde, myelopreoxidase activity and the generation of reactive oxygen species were increased in the cardiac tissue. On the other hand, RVT markedly ameliorated the severity of cardiac dysfunction, while all oxidant responses were prevented; implicating that RVT may be of therapeutic use in preventing oxidative stress due to DOX toxicity.
Keywords: Doxorubicin; toxicity; resveratrol; free radical; ADRIAMYCIN-INDUCED CARDIOTOXICITY; INDUCED HEART-FAILURE; RED WINE; NITRIC-OXIDE; INDUCED CARDIOMYOPATHY; MOLECULAR-MECHANISM; ANTIOXIDANT ENZYMES; LIPID-PEROXIDATION; CARDIAC TOXICITY; RATS